Enhancing community economies through legal protection models of traditional knowledge and cultural expressions: a study on Indonesia's communal intellectual property framework - Widiarsa, Anang Pratama; Mayasari, Hanita (Institut Seni Indonesia Surakarta, 2024)
This research investigates the impact of legal protection models for Traditional Knowledge and Traditional Cultural Expressions (TKTCE) on the economic development of communities in Indonesia. It emphasizes the government's role in regulating TKTCE as an integral component of communal intellectual property (CIP) that can be effectively integrated into the national development framework. The study employs a juridical-normative approach, utilizing both primary and secondary legal materials, which were collected through comprehensive literature reviews and analyzed descriptively and qualitatively. This research highlights significant gaps in the current regulatory framework, particularly the inadequacies in international conventions that have led to economic losses for Indonesia. The findings indicate that the government's recent initiatives, including Government Regulation Number 56 of 2022, aim to enhance protective measures for TKTCE, thereby fostering a creative ecosystem that benefits local communities. This research is crucial as it addresses the intersection of legal protection, cultural expression, and economic improvement, providing insights into how effective legal frameworks can empower communities and preserve cultural heritage.